Killing of Staphylococcus aureus in murine macrophages by chloroquine used alone and in combination with ciprofloxacin or azithromycin - Dey S (Dove Medical Press, 2015)
Somrita Dey, Biswadev BishayiDepartment of Physiology, Immunology Laboratory, University of Calcutta, University Colleges of Science and Technology, Calcutta, IndiaAbstract: This study aimed to determine any alteration in the killing of Staphylococcus aureus in murine peritoneal macrophages when chloroquine (CQ) is used alone compared with when it is used in combination with ciprofloxacin (CIP) or azithromycin (AZM). The study also aimed to find out the implication of reactive oxygen species (ROS) production and cytokine release in the intracellular killing of S. aureus in macrophages. We present here data obtained with a model of S. aureus-infected mouse peritoneal macrophages in which the intracellular growth of the bacteria and the influence of antibiotics was monitored for 30, 60, and 90 minutes in the presence or absence of CQ along with the production of ROS and alteration in levels of antioxidant enzymes and cytokines. It was observed that S. aureus-triggered cytokine response was regulated when macrophages were co-cultured with CQ and AZM as compared with CQ stimulation only. It can be suggested that action of AZM in mediating bacterial killing is enhanced by the presence of CQ, indicating enhanced uptake of AZM during early infection that may be essential for bacteria killing by AZM. Reduction of oxidative stress burden on the S. aureus-infected macrophages may pave the way for better killing of internalized S. aureus by CQ plus ciprofloxacin (CIP) or CQ plus AZM. Based on these observations, one may speculate that in an inflammatory milieu, CQ loaded with AZM elicits a stronger proinflammatory response by increasing the intracellular uptake of AZM or CIP, thus enabling the immune system to mount a more robust and prolonged response against intracellular pathogens.Keywords: azithromycin, ciprofloxacin, intracellular survival